2004
DOI: 10.1021/ja039296+
|View full text |Cite
|
Sign up to set email alerts
|

Highly Polarized Luminescence from Optical Quality Films of a Semiconducting Polymer Aligned within Oriented Mesoporous Silica

Abstract: In this Communication, we show that nanometer scale control of semiconducting polymer chain conformation is possible using host/guest chemistry in highly ordered and macroscopically oriented thin films of mesoporous silica. This control leads to a thin film composite material that is optically transparent, densely filled with polymer, and has highly polarized optical properties. Calculations of absorption and emission anisotropies further indicate full incorporation of the polymer into the nanoscale pore space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
132
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(134 citation statements)
references
References 22 publications
2
132
0
Order By: Relevance
“…For example, Miyata and Tolbert et al reported alignment control of semiconducting polymers using uniaxially aligned mesoporous silica films. 25), 26) The semiconducting polymer was well aligned along the uniaxial mesochannels. The polymer/silica composite film showed the polarized absorption and fluorescence caused by aligned polymers.…”
mentioning
confidence: 99%
“…For example, Miyata and Tolbert et al reported alignment control of semiconducting polymers using uniaxially aligned mesoporous silica films. 25), 26) The semiconducting polymer was well aligned along the uniaxial mesochannels. The polymer/silica composite film showed the polarized absorption and fluorescence caused by aligned polymers.…”
mentioning
confidence: 99%
“…Tolbert et al also succeeded in alignment control of semiconducting polymers inside uniaxially aligned mesochannels. 460,461 The semiconducting polymer was aligned along the uniaxial mesospace, showing strong polarized absorption and fluorescence. Moreover, the confinement leads to low-threshold amplified spontaneous emission from the aligned polymer chains.…”
Section: Mesoporous Non-siliceous Filmsmentioning
confidence: 99%
“…This is probably caused by the weaker hydrophobic interaction of C 10 EO 10 and C 12 EO 10 with the rubbing-treated polyimide surface due to their shorter alkyl chains. 8 To find optimum synthetic conditions of the films with the aligned mesochannels, we performed a systematic analysis of the ª2ª XRD profiles. We subtracted the profile recorded under the geometry in which the X-rays were parallel to the rubbing direction from that recorded under the perpendicular geometry, in order to extract the anisotropy of the diffraction peaks.…”
Section: ¹1mentioning
confidence: 99%
“…8,9 Several methods to control the alignment of the mesochannels have been reported. 1017 Among them, the method in our previous report using a substrate with a rubbing-treated polyimide layer combined with evaporation-induced self-assembly (EISA) can control the mesochannel direction within the º distribution of 3°at macroscopic scales.…”
mentioning
confidence: 99%
See 1 more Smart Citation